2017
DOI: 10.1002/1873-3468.12905
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of nuclear pore complex assembly – two different ways of building one molecular machine

Abstract: The nuclear pore complex (NPC) mediates all macromolecular transport across the nuclear envelope. In higher eukaryotes that have an open mitosis, NPCs assemble at two points in the cell cycle: during nuclear assembly in late mitosis and during nuclear growth in interphase. How the NPC, the largest nonpolymeric protein complex in eukaryotic cells, self‐assembles inside cells remained unclear. Recent studies have started to uncover the assembly process, and evidence has been accumulating that postmitotic and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
124
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 108 publications
(171 reference statements)
2
124
0
Order By: Relevance
“…We thus 139 asked, if replicatively aged cells start to progressively accumulate misassembled NPCs. Correct NPC 140 assembly is assisted by several proteins that are temporarily associated with NPCs during the assembly 141 process (Dawson et al, 2009;Lone et al, 2015;Otsuka and Ellenberg, 2018;Scarcelli et al, 2007;142 Webster et al, 2016;Zhang et al, 2018). Amongst these are (i) Heh1 and Heh2, the orthologues of 143 human LEM2 and Man1, which are known to be involved in recognition of misassembled pores 144 (Webster et al, 2014(Webster et al, , 2016, (ii) Vps4, an AAA-ATPase with multiple functions amongst which the 145 clearance of misassembled NPCs from the NE (Webster et al, 2014) and (iii) Apq12, Rtn1 and Rtn2,146 Brr6 and Brl1 membrane proteins of the NE-ER network that are involved in NPC assembly, possibly 147 through roles in modulating membrane curvature (Lone et al, 2015;Scarcelli et al, 2007;Zhang et al, 148 2018).…”
Section: Figmentioning
confidence: 99%
“…We thus 139 asked, if replicatively aged cells start to progressively accumulate misassembled NPCs. Correct NPC 140 assembly is assisted by several proteins that are temporarily associated with NPCs during the assembly 141 process (Dawson et al, 2009;Lone et al, 2015;Otsuka and Ellenberg, 2018;Scarcelli et al, 2007;142 Webster et al, 2016;Zhang et al, 2018). Amongst these are (i) Heh1 and Heh2, the orthologues of 143 human LEM2 and Man1, which are known to be involved in recognition of misassembled pores 144 (Webster et al, 2014(Webster et al, , 2016, (ii) Vps4, an AAA-ATPase with multiple functions amongst which the 145 clearance of misassembled NPCs from the NE (Webster et al, 2014) and (iii) Apq12, Rtn1 and Rtn2,146 Brr6 and Brl1 membrane proteins of the NE-ER network that are involved in NPC assembly, possibly 147 through roles in modulating membrane curvature (Lone et al, 2015;Scarcelli et al, 2007;Zhang et al, 148 2018).…”
Section: Figmentioning
confidence: 99%
“…He compared post-mitotic NPC assembly during telophase to NPC assembly within existing nuclear envelopes during interphase (i.e., without or with the pre-existing double nuclear membrane, respectively). Using endogenously tagged nucleoporins he demonstrated that these mechanisms are strikingly different: the initial steps of both processes may rely on transmembrane nucleoporin POM121 and the 10-subunit Y-subcomplex scaffold of the NPC, the timing and order of subsequent recruitment of other nucleoporins differs dramatically between the two events [5].…”
Section: Nuclear Pores and Their Functionmentioning
confidence: 99%
“…A further challenge in the design of self‐assembling proteins is to control the assembly process. Natural multimeric proteins such as actin, the vertebrate nuclear pore complex, and some viral capsids undergo environmentally responsive assembly and disassembly. Inspired by Nature , various strategies have been developed to control the assembly of extended protein‐based nanomaterials that form filaments, 2D lattices, and 3D crystals .…”
Section: Introductionmentioning
confidence: 99%